2022
DOI: 10.1128/mbio.01612-22
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose of Anti-HBsAg Antibody-Encoding mRNA-LNPs Suppressed HBsAg Expression: a Potential Cure of Chronic Hepatitis B Virus Infection

Abstract: It is the first time that mRNA-LNPs have been used to express anti-HBsAg antibodies (G12-scFv, G12-scFv-Fc, and G12-IgG). G12-scFv-Fc- and G12-IgG-encoding mRNA-LNPs exerted a sustained effect on HBsAg serum clearance in the adeno-associated virus (AAV)/HBV mouse model with persistent HBsAg expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The results showed that the injection of a single dose of LNPs containing both G12-scFv-Fc mRNA and G12-IgG mRNA significantly reduced the serum HBsAg level in treated mice within 30 days. 206 Hepatitis C virus (HCV). Dallas et al utilized short synthetic shRNA (sshRNA)-encapsulated LNPs to silence the expression of genes associated with the HCV internal ribosome entry site.…”
Section: (C) and (D))mentioning
confidence: 99%
“…The results showed that the injection of a single dose of LNPs containing both G12-scFv-Fc mRNA and G12-IgG mRNA significantly reduced the serum HBsAg level in treated mice within 30 days. 206 Hepatitis C virus (HCV). Dallas et al utilized short synthetic shRNA (sshRNA)-encapsulated LNPs to silence the expression of genes associated with the HCV internal ribosome entry site.…”
Section: (C) and (D))mentioning
confidence: 99%
“… 101 Additionally, mRNA vaccines offer a novel approach for chronic virus infections such as HBV. 102 A mRNA-based vaccine for treating Hepatitis B virus-associated hepatocellular carcinoma (HCC) (NCT05738447) is currently undergoing clinical trial.…”
Section: Classifying Mrna Cancer Vaccinesmentioning
confidence: 99%
“…The use of mRNA to encode antibody transgenes has been tested for a multitude of indications, including pathogens [51,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74], toxins [65,75,76], and cancers [65,[77][78][79][80][81][82] (Table 2. Current approaches for mRNA delivery of antibodies).…”
Section: Modified Mrna For Delivery Of Broadly Neutralizing Antibodiesmentioning
confidence: 99%